Distribution of ESBL-producing and carbapenem-resistant E. coli and Salmonella spp. in retail chicken meat and live bird market sewage in Bangladesh - Mst. Sonia Parvin; Sudipta Talukder; Sayra Tasnin Sharmy; Md. Mehedi Hasan; Md. Taohidul Islam (PLoS ONE, 2026)
A cross-sectional live bird market (LBM) survey was conducted to determine the prevalence and distribution of extended-spectrum β-lactamase (ESBL)-producing and carbapenem-resistant (CR) E. coli and Salmonella spp. in retail chicken meat and LBM sewage in Bangladesh. E. coli and Salmonella spp. were identified using culture-based and molecular methods. Isolates were tested for CR by a disk diffusion test; a confirmatory ESBL screening was performed by double disk synergy test. The isolates were screened for ESBL and CR genes using PCR. Prevalence of ESBL- E. coli and Salmonella spp. in retail chicken meat was 70% and 43.4%, respectively while in LBM sewage, it was 79.7% and 28.1%, respectively. Carbapenem resistance was also common, detected in 54.1% and 46.9% of E. coli and 37.2% and 12.5% of Salmonella spp. isolated from retail chicken meat and LBM sewage, respectively. Molecular analysis revealed the presence of ESBL and CR genes, including bla CTX-M-1 , bla CTX-M-2 , and bla NDM-1 . The bla CTX-M-1 gene was detected at low frequencies among ESBL- E. coli from retail chicken meat (1.3%) and LBM sewage (3.9%), and among ESBL- Salmonella spp. from retail chicken meat (3.6%), while bla CTX-M-2 was identified in a single ESBL- E. coli isolate from LBM sewage. Notably, bla NDM-1 was detected in 5.2% of CR- E. coli and 33.6% of CR- Salmonella spp. from retail chicken meat. Multidrug resistance (MDR) was observed in 98.2% and 92.2% of ESBL- E. coli , and 97.8% and 94.4% of ESBL- Salmonella spp. from retail chicken meat and LBM sewage, respectively; while, 98.8% and 100% of CR- E. coli , and 97.5% and 87.5% of CR- Salmonella spp. from both types of samples, respectively were MDR. These results highlight the urgent need for strengthened antibiotic stewardship, regular surveillance, and improve biosecurity in live bird markets in Bangladesh.